Enhancing Young Learners’ English Vocabulary Mastery Through Animal Quest Gamification - Noviarini, Tiara; Paderan, Mark Philip Castillo; Hamdani, Zohri; Fransiska, Fini Widya; Fitriani, Dhafiya (JOLLT Journal of Languages and Language Teaching, 2026)
English language acquisition is indispensable for cultivating communication competencies and fostering intercultural understanding from an early stage. However, Indonesian elementary students frequently encounter difficulties in vocabulary mastery due to repetitive instructional approaches and a deficiency of engaging, visual media tailored to young learners’ concrete learning styles. This research examines the efficacy of the gamified media, Animal Quest, in enhancing students’ English vocabulary. Employing a quantitative quasi-experimental methodology, forty first-grade students at SD Negeri 5 Pringsewu Barat were divided into an experimental group and a control group. Data were collected through pre-tests and post-tests and subsequently analyzed using SPSS 25.0 with paired and independent t-tests. The findings reveal a statistically significant improvement within the experimental group, which demonstrated a higher mean post-test score (87.05) compared to the control group (70.20). These results imply that gamification via Animal Quest effectively enhances vocabulary acquisition, engagement, and motivation among young learners. Furthermore, the study underscores that gamified storytelling media can serve as a valuable instructional innovation within primary English education, aligning with the objectives of the Merdeka Belajar curriculum and encouraging educators to adopt more interactive, student-centered pedagogical practices.